Telecommunication Networks Trends and Developments - Abdul Matin, Mohammad (IntechOpen, 2019)
The demand for advance telecommunication services has increased dramatically over the last few years. This has led to technological changes with revolutionized engineering strategies to optimize network construction and operation. Telecommunication networks integrate with a wide range of technologies, including optical amplifiers, software architectures for network control and management, abstract algebra required to design error correction codes, and network modeling. This book presents research contributions towards new techniques, concepts, analysis of the telecom market's evolving trends, and infrastructure to provide integrated voice, data, and video communications services that are critical to the operation and competitiveness of companies, governments, and other organizations.